2013
DOI: 10.1007/s13311-012-0165-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Anti-inflammatory Properties of a Coffee Component in the MPTP Model of Parkinson's Disease

Abstract: Consumption of coffee is associated with reduced risk of Parkinson's disease (PD), an effect that has largely been attributed to caffeine. However, coffee contains numerous components that may also be neuroprotective. One of these compounds is eicosanoyl-5-hydroxytryptamide (EHT), which ameliorates the phenotype of α-synuclein transgenic mice associated with decreased protein aggregation and phosphorylation, improved neuronal integrity and reduced neuroinflammation. Here, we sought to investigate if EHT has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 44 publications
(57 reference statements)
3
52
0
Order By: Relevance
“…Levels of PP2A methylation are controlled by a balance between the activities of two highly conserved, PP2A-specific, enzymes: a methyl transferase, PPMT, that transfers methyl groups from S-adensylmethionine to the PP2A carboxy terminus; and a methyl esterase, PME, that demethylates PP2A. EHT was initially identified as a component in coffee extracts that inhibited the PP2A demethylation reaction (Lee et al 2013). Dramatic increases in PP2A demethylation have been observed in brains from AD patients (Sontag et al 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of PP2A methylation are controlled by a balance between the activities of two highly conserved, PP2A-specific, enzymes: a methyl transferase, PPMT, that transfers methyl groups from S-adensylmethionine to the PP2A carboxy terminus; and a methyl esterase, PME, that demethylates PP2A. EHT was initially identified as a component in coffee extracts that inhibited the PP2A demethylation reaction (Lee et al 2013). Dramatic increases in PP2A demethylation have been observed in brains from AD patients (Sontag et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacokinetic studies delivering [ 3 H]-EHT intraperitoneally revealed that this compound crosses the blood brain barrier achieving levels sufficient to inhibit PP2A demethylation, indicating its feasibility for proof of concept studies (Lee et al 2011). EHT was identified as the major PP2A demethylation inhibitor in coffee (Lee et al 2011) and was reported to be effective in preclinical studies (Lee et al 2011; Lee et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH and GSSG were measured in the substantia nigra and cerebral cortex by using a GSH assay kit (Cayman) with enzymatic recycling, as previously described (39). Absorbance was measured at 405 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine, by blocking A 2A R, is able to prevent synaptotoxicity, excitotoxicity and neuronal loss18192021. In addition, it has also been reported that caffeine has anti-inflammatory properties in the CNS22, namely by attenuating microglia-mediated neuroinflammation23.…”
mentioning
confidence: 99%